Human brain cancer studied by resonance Raman spectroscopy - Zhou, Yan; Liu, Cheng-Hui; Sun, Yi; Pu, Yang; Boydston-White, Susie; Liu, Yulong; Alfano, Robert R. (Journal of biomedical optics, 2012)
The resonance Raman (RR) spectra of six types of human brain tissues are examined using a confocal micro-Raman system with 532-nm excitation in vitro. Forty-three RR spectra from seven subjects are investigated. The spectral peaks from malignant meningioma, stage III (cancer), benign meningioma (benign), normal meningeal tissues (normal), glioblastoma multiforme grade IV (cancer), acoustic neuroma (benign), and pituitary adenoma (benign) are analyzed. Using a 532-nm excitation, the resonance-enhanced peak at 1548  cm-1 (amide II) is observed in all of the tissue specimens, but is not observed in the spectra collected using the nonresonance Raman system. An increase in the intensity ratio of 1587 to 1605  cm-1 is observed in the RR spectra collected from meningeal cancer tissue as compared with the spectra collected from the benign and normal meningeal tissue. The peak around 1732  cm-1 attributed to fatty acids (lipids) are diminished in the spectra collected from the meningeal cancer tumors as compared with the spectra from normal and benign tissues. The characteristic band of spectral peaks observed between 2800 and 3100  cm-1 are attributed to the vibrations of methyl (─CH3) and methylene (─CH2─) groups. The ratio of the intensities of the spectral peaks of 2935 to 2880  cm-1 from the meningeal cancer tissues is found to be lower in comparison with that of the spectral peaks from normal, and benign tissues, which may be used as a distinct marker for distinguishing cancerous tissues from normal meningeal tissues. The statistical methods of principal component analysis and the support vector machine are used to analyze the RR spectral data collected from meningeal tissues, yielding a diagnostic sensitivity of 90.9% and specificity of 100% when two principal components are used.